Identifying the Credentials of Agricultural Seeds in Modern Era - Naveenkumar M, Srithar S, Vijayaganth V, Ramesh kalyan G (International Journal of Advanced Science and Technology, 2020)
Agriculture plays an energetic part in the Indian economy. Seed is a key source for the development of agriculture. Seeds are of two types: hybrid seeds and country seeds. Non-hybrid seeds were in existence during the past decades, they were enriched with carbohydrates, vitamins, proteins, and minerals etc. Now-a-days, these seeds are becoming endangered, on the effect of this, the hybrid seeds came into existence. Farmers get a huge amount of output from the hybrid seeds, but these seeds are of low value in terms of carbohydrates, vitamins, proteins and minerals etc. On consuming these seeds, the immune system of the human body gets weaker. An analysis is to be made in order to depict the value of the seeds and their outcome. The output will be previewing the differentiation of both the scenarios.